Marketing Motivation Influencing Higher Education Students’ Traveling to Participate in Electronic Sports Events - Poltanee , Issarapong; Boonphetkaew , Umaporn (Business Administration and Management Journal Review, 2022)
This research aimed to study the online gaming behavior and the motivation of marketing mix including factors that influence higher education students’ decision to travel to participate in Electronic Sports Events. The data were collected from a sample of 200 people using accidental sampling method to analyze the data with descriptive statistics and inferential statistics to explain the prediction of variables used in the study by means of multiple regression analysis. The results of the research according to the research related to online gaming behaviors, it was found that most of the students had been playing online games for 5 years or more. The average time spent on playing online games was 4 - 6 times per week with the time spent on playing online games between 20.01 - 24.00 and most of them played online games at home or at a dormitory, and played online alone for entertainment and stress relief. It was found that the independent variables that had the power to predict the attracting factors influencing the decision to travel to participate in Electronic Sports Events the most were overall satisfaction, experiences gained from participating in Electronic Sports Events, and the intention of introducing the events, respectively.